Reasons and rationalizations : the limits to organizational knowledge - Argyris, Chris, 1923-2013 (Oxford University Press, 2006)
What is the purpose of social science and management research? Do scholars/researchers have a responsibility to generate insights and knowledge that are of practical (implementable) value and validity? The author questions many of the assumptions of organizational theory and research.